CONSIDERATIONS ON EXCESSIVE LIBERALITIES REDUCTION - ILIOARA GENOIU (Challenges of the Knowledge Society)
Reduction of excessive liberalities represents one of the sanctions typical to succession field, which operates, on demand, as a result of forced heirship being transgressed. The present work is aimed to analyze all the issues regarding this sanction, under all the aspects which the latter involves, in the light of the current Civil Code1. Thus, there will be analyzed elements such as: the way reduction operates, persons who can demand it, ways of performing reduction, statute of limitations term, order in which reduction is performed, legal effects and reduction of some special liberalities. The present work will also provide a comparative analysis of reduction, by pointing out the novelty elements brought in the field under discussion by the current Civil Code, in comparison with the 1864 Civil Code. In general, when it comes to forced heirship, the current Civil Code consecrates several novelty elements, reconfiguring the matter in question. These modern elements also concern the excessive liberalities reduction issue. Consequently, one of the objectives of the current work is to point out such novelties and to assess their modern character.